A Wilhelmine von Zenge. Würzburg, den 10. (und 11.) Oktober 1800 - Kleist, Heinrich von (FLOEMA. Caderno de Teoria e História Literária, 2017)
A Wilhelmine von Zenge. Würzburg, den 10. (und 11.) Oktober 1800